Online service quality of m-commerce: effect on user satisfaction - Ismail, Azman; Arshad, Mohd. Mursyid; Saros, Angela; Ibrahim, Zalina; Sharif, Sabariah (Research Trend, 2020)
In an era of 4th industrial revolution, online service quality of m-commerce is used as an essential innovator strategy to accomplish public and private organizations’ strategies and goals. This latest development reflects the importance of this research. The primary objective of this study is to evaluate the correlation between online service quality of m-commerce and user satisfaction. Survey questionnaires were used to collect data from Grabcar’s users in Malaysia. The Statistical Package for Social Science (SPSS) was used to determine the quality of research instrument and test the research hypotheses. The results of linear regression analysis proved that user satisfaction is an important outcome of the online service quality of mcommerce. This result can be used as essential recommendations by practitioners to understand diverse perspectives of online service quality of m-commerce and formulate online service quality operations based on user demands to maintain and enhance the organizational competitiveness and performance in times of global competition and economic instability.